Zmierzch bogów w Dubrowniku - Pająk, Patrycjusz (Wydawnictwo Naukowe UAM, 2013)
The Croatian film Occupation in 26 pictures(1978), directed by Lordan Zafranovićis considered as one of the most controversial vision of the Second World War in Yugoslav cinema. The director uses the ornamental style, modeled on Italian cinema, to portray the change of power in Dubrovnik in 1941 – at the beginning of the fascist occupation of the city. He juxtaposes the licentiousness of Italian, German and Croatian fascists and the fall of the Dubrovnik aristocracy and the rebellion of communists. The political changes in the city are presented against the background of its rich cultural tradition. Zafranović highlights the beauty of Dubrovnik’s architectural and natural landscape that fascists desecrate. Decadent poetics with its aesthetic excess allows him to refresh and deepen the communist interpretation of the fascist occupation.
Twilight of the Gods in Dubrovnik
Keywords: Zafranović; Dubrovnik; Croatian film; Yugoslav film; power; fascism; aristocracy; communism